Carrier transport and surface potential over phase variations in the surface and bulk of highly efficient Cu2ZnSn(S, Se)4 solar cells. (24th January 2020) - Kim, Juran; Kim, Jayeong; Ko, Eunji; Yoon, Seokhyun; Sim, Jun‐Hyoung; Yang, Kee‐Jeong; Kim, Dae‐Hwan; Kang, Jin‐Kyu; Song, Yu Jin; Jeon, Chan‐Wook; Jo, William
Abstract: We report highly efficient Cu2 ZnSn(S, Se)4 (CZTSSe) thin films with a power conversion efficiency (PCE) of 12.3% at their surface and interface. The structural and electrical properties were locally investigated, using scanning probe microscopy and micro‐Raman scattering, to improve the performance of kesterite solar cells. Interestingly, this research reports quite different results from the conventional kesterite solar cells, owing to the observance of undesirable voids and secondary phases. Nonetheless, the solar cells exhibit a high PCE of over 12%. Thus, we probe the kesterite solar cells as a function of the depth and introduce a mechanical dimple‐etching process. The relatively low melting temperature of the pure‐metal precursors results in the unique properties within the solar cell materials. Understanding these phenomena and their effects on carrier behavior enables the achievement of a higher PCE and better performance for kesterite solar cells. Abstract : The high‐efficient kesterite thin film, grown by pure‐metal precursors, has unique phase distribution through the thin film, compared to the one by S compound precursors. The CZTSSe thin films show secondary phases and few voids between the absorber and the Mo layer. The altered current flow path in the solar cells, however, can result in the enhanced solar cell efficiency.